Simultaneous removal of anions using moringa-functionalized adsorbents - Barajas, John Raymond B. (Animo Repository, 2016)
Nitrates, phosphates, and many other anionic chemical species are among the most problematic and widespread contaminants in water sources. Currently, technologies for removing them in water involve biological and physico-chemical processes. In this study, we test the extent to which the cationic protein from Moringa Oleifera (MO) seeds can effectively sequester anionic contaminants in water. The protein was isolated from the MO seed through selective adsorption onto two carbon adsorbents: rice husk ash and commercial activated carbon. This step was designed to eliminate the co-release of soluble organics in MO seeds, which can shorten the storage life of the treated water. The MO-functionalized adsorbents were then tested for their removal efficiency of five anions: chloride, nitrite, nitrate, phosphate and sulfate. A semi-factorial experimental design was adopted to evaluate the effect of contact time and adsorbent dose on the anion removal efficiencies. As a control, experiments were also run in parallel using bare carbon adsorbents. The aqueous MO protein concentrations were measured using an optical density meter (280 nm) and ion concentrations were measured using an ion chromatograph. ANOVA analysis was performed to determine the effectiveness of Moringa-functionalized carbon adsorbents compared to bare carbon adsorbents. Results show that MO protein adsorbs well on the carbon adsorbents, and that adsorption is higher in activated carbon than in rice husk. Equilibrium is achieved at 20 minutes of contact time. In all adsorbents (bare and MO-functionalized), the highest anion removal rate was observed for nitrate. Anion removal rates were generally higher in MO-functionalized adsorbents than in bare adsorbents. Phosphate removal was only observed in the MO-functionalized adsorbents, although it is noted that rice husk ash contained large amounts of soluble phosphate that contributed to a net positive increase of phosphate levels in the water. Overall, these findings suggest a strong potential for using MO protein as a low-cost water treatment technology, for example, in removing anionic dyes and surfactants. Further studies are needed to examine the surface interactions among anions, carbon adsorbents, and MO protein. © 2016 IEEE.